Pengembangan E-Modul Berbasis Flipbook Tema Selamatkan Makhluk Hidup - Hasriani, Hasriani; Baderiah, Baderiah; Bungawati, Bungawati; Wiratman, Arwan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to determine the validity and practicality of a flipbook-based e-module with the theme Save Living Creatures for class VI SDN 525 Labembe. A type of research used is Research and Development (R&D) using the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, interviews, documentation, and questionnaires. The data obtained was analyzed qualitatively and quantitatively. This research produced a product in the form of a flipbook-based e-module on material about saving living creatures in class VI at SDN 525 Labembe, Ponrang District, Luwu Regency and was validated by 3 validators. The language validator reached a percentage of 92% (very valid), the material validator reached 84.3% (very valid), and the design validator reached 96.8% (very valid) and the average of the three validations was 89.7% with the very category valid. The teacher's practicality test results were 91% (very practical) and the students' practicality test results were 85.50% (very practical). The media developed is included in the valid category, which means that the results obtained are a source of accurate and relevant information in accordance with the research objectives